XXIX Seminário Internacional de Formação de Professores para América Latina: democracia e diversidade: Anais resumos expandidos; 24, 25 e 26 de novembro de 2021. - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present work aims to discuss how the National Common Curricular Base ± BNCC and Curriculum Paulista address the theme of industry and innovation in these two new curricula implemented in 2018 and 2019 respectively, as well as the methodologies that teachers can offer so that the competencies and skills presented in these two documents can developed among students. Birigui is nationally known as the National Capital of Children's Footwear, therefore, it is clear that the economy and the territorial arrangement of this municipality are largely linked to footwear companies. then talk of industries and industrial innovation, especially footwear, is to bring the content of the classes to reality of students, since the vast majority of their family members work in these companies. In this way, the field work carried out in a footwear company comes to solidify the knowledge acquired in the classroom, presenting to all students, in an empirical way, what accompanies them in home and the discussions held in Geography classes.
XXIX International Seminar on Teacher Training for Latin America: Democracy and Diversity: Anais Full Articles ; 24th, 25th and 26th of November from 2021
Keywords: Educação; Ensino Superior; Universidade Pública; Educação Básica; Education; Teachers - Training; University education; Basic education; CNPQ::CIENCIAS HUMANAS